1992
DOI: 10.1099/0022-1317-73-7-1615
|View full text |Cite
|
Sign up to set email alerts
|

Early embryo invasion as a determinant in pea of the seed transmission of pea seed-borne mosaic virus

Abstract: Seed transmission of an isolate of pea seed-borne mosaic virus (PSbMV) in several pea genotypes has been studied. Cross-pollination experiments showed that pollen transmission of PSbMV did not occur and accordingly, virus was not detected in pollen grains by ELISA or electron microscopy. Comparative studies between two pea cultivars, one with a high incidence of seed transmission and one with none, showed that PSbMV infected the floral tissues (sepals, petals, anther and carpel) of both cultivars, but was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 14 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…Because pathogens must cross several barriers intended to protect the developing embryo, the occurrence of narrow population bottlenecks during pathogen vertical transmission could be a quite general rule. The capacity of viruses to invade plant embryos and withstand seed maturation and desiccation depends both on virus and host genotypes, as demonstrated for PSbMV [23], [27], [39]. Seed transmission of PSbMV in pea occurs exclusively by direct invasion of immature embryos from virus-infected maternal tissues.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Because pathogens must cross several barriers intended to protect the developing embryo, the occurrence of narrow population bottlenecks during pathogen vertical transmission could be a quite general rule. The capacity of viruses to invade plant embryos and withstand seed maturation and desiccation depends both on virus and host genotypes, as demonstrated for PSbMV [23], [27], [39]. Seed transmission of PSbMV in pea occurs exclusively by direct invasion of immature embryos from virus-infected maternal tissues.…”
Section: Discussionmentioning
confidence: 97%
“…Such conditions are therefore favorable to the occurrence of strong virus population bottlenecks. Early infection of the mother plant is necessary for PSbMV vertical transmission to occur [23]. PSbMV invasion of pea embryos occurs from virus infection spreading from the maternal cells in the micropylar region of the embryo to the endosperm cytoplasm, then to the embryonic suspensor and finally to the embryo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seeds produced from SPLCV‐infected floral tissues clearly tested positive for SPLCV. According to previous studies concerning seed transmission of viruses such as Apple latent spherical virus , PSbMV and Cucumber mosaic viru s (CMV), the invasion route of virus to seed (especially invasion to embryo) was the most important determinant of seed transmission (Wang & Maule, ; Yang et al ., ; Nakamura et al ., ). In the present study, PCR tests showed that SPLCV was located inside the seed, indicating that SPLCV can be a seedborne virus and can be transmitted from seeds to a next‐generation plant via the embryo.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that several virus-host factor interactions determine the spread and accumulation of PSbMV in the maternal testa tissue. Whereas PSbMV can enter the embryo after fertilization (Wang & Maule, 1992), seed transmission of BSMV depends mainly on the ability of the virus to reach the reproductive tissues prior to fertilization (Edwards, 1995). Despite this difference, replication and movement also play central roles in seed transmission of BSMV, the major determinants being the RNA~ 5' UTR, a 369 repeat in the 7a gene, and the 7b gene.…”
Section: Seed Transmission Of Vp-1114 Vp-1144 Vp-4144 and Vp-4111 Imentioning
confidence: 99%